A Sequential Dual-Reagent Paper-Based Analytical Device with Structural Release Control for Point-of-Care Detection of Urinary N‑Acetyl-β‑d‑Glucosaminidase - Jie Cheng (294193) (2025)
N-acetyl-β-d-glucosaminidase (NAG) is an important biomarker that indicates early renal tubular damage. Its activity level in urine has been widely used for early detection and monitoring of chronic kidney disease (CKD), particularly diabetic nephropathy. However, current detection methods rely on complex instrumentation, which hinders their suitability for point-of-care testing (POCT) that requires portability and user-friendliness. To address this challenge, we developed a sequential dual-reagent paper-based analytical device (SeDR-PAD) that utilizes structural partitioning and a delayed-trigger mechanism to achieve time-programmed control of the NAG enzymatic reaction and color development process. The system uses VRA-GlcNAc as the substrate to generate a chromogen under the catalysis of NAG. A portable device then releases an alkaline catalyst after a programmed delay to initiate color development, followed by optical quantitative analysis. This method provides a linear detection range of 0–200 U/L, with a detection limit of 0.524 U/L and high reproducibility (CV < 6%, n = 5). In a methodological comparison involving 70 clinical urine samples, the SeDR-PAD platform demonstrated strong concordance with the standard clinical method, with a correlation coefficient R2 of 0.9833. These findings highlight the strong potential of SeDR-PAD for clinical POCT of uNAG in individuals at high risk for kidney disease.